CCT4 knockdown enhances the sensitivity of cisplatin by inhibiting glycolysis in human esophageal squamous cell carcinomas. Issue 11 (14th September 2022) - Fang, Jiarui; Ma, Yingchao; Li, Ya; Li, Jianhui; Zhang, Xishen; Han, Xiao; Ma, Shanshan; Guan, Fangxia
Abstract: Esophageal squamous cell carcinoma (ESCC) is a common human malignancy characterized by late‐stage diagnosis, metastasis, and poor prognosis. Cisplatin (DDP)‐based chemotherapy has been the most predominant treatment for patients with ESCC. However, the high rate of DDP resistance and toxicity seriously hinder its clinical application. Then, the optimized strategy and mechanisms for ESCC to enhance DDP sensitivity are in great demand. Accumulating evidence have shown that chaperone proteins are closely related to the tumorigenesis and drug resistance of cancers. Chaperonin containing TCP1 complex 4 (CCT4) is a recent identified member of the family. However, its expression and function in ESCC have not been well illustrated. In this study, we found that CCT4 was highly expressed in human ESCC tissues and cell lines, and closely related to the poor prognosis. Moreover, CCT4 silence raised oxidative stress and inhibited glycolysis of ESCC cells, which significantly inhibited cell proliferation and migration, promoted apoptosis and caused cell cycle arrest in ESCC cells. Interestingly, CCT4 knockdown enhanced the sensitivity of KYSE150 cells to DDP by regulating AMPK/AKT/Nrf2 signaling pathway and inhibiting glycolysis ability. Taken together, our results indicate that targeting CCT4 may be a therapeutic target in ESCC patients, which provides a theoretical basis to enhance the sensitivity of DDP in ESCC. Abstract : The possible mechanism of CCT4 knockdown enhancing the sensitivity of ESCC to DDP by inhibiting glycolysis